2099. Catheter-related Staphylococcus aureus Bacteremia and Septic Thrombosis: The Role of Anticoagulation and Duration of Intravenous Antibiotic Therapy. (26th November 2018) - Dib, Rita Wilson; Chaftari, Anne-Marie; Hachem, Ray Y; Jiang, Ying; Dandachi, Dima; Raad, Issam
Abstract: Background: Catheter-related septic thrombosis is suspected in patients with persistent Central Line-associated Blood Stream Infection (CLABSI) after 72 hours of appropriate antimicrobial therapy. There are limited data outlining the characteristics of the disease and the adequate duration of antimicrobials. In addition, the role of anticoagulation in the management of septic thrombosis remains unclear. We herein studied the clinical characteristics of staphylococcus aureus catheter-related septic thrombosis as well as the appropriate management and duration of treatment. Methods: We conducted this retrospective study where we included patients with CLABSI due to Staphylococcus aureus who had a concomitant radiographic evidence of thrombosis at the level of catheter placement between the years 2005 and 2017. We collected data pertaining to patients' medical history, clinical presentation, management, treatment and outcome within 3 months of bacteremia onset. Failure was defined as persistence of signs and symptoms at 72 hours, persistence bacteremia at 48–96 hours, relapse, complications or overall mortality. Results: A total of 128 patients were included. The median age was 55 years. Total relapse/recurrence rate was 8% and all-cause mortality within 3 months was 16%. We found no significant difference in overall outcome between patients who had deep vs. superficial thrombosis. Patients with superficial thrombosis were found to have higher rate of pulmonary complications (25% vs. 6%; P = 0.01) compared with those with deep thrombosis. Patients who received less than 28 days of intravascular antibiotic therapy had higher all-cause mortality (31 vs. 5% P = 0.001). A multivariate logistic regression analysis identified two independent predictors of treatment failure: presence in the ICU at any point during their illness (odds ratio (OR) = 2.74, 95% confidence interval (CI) = 1.08–6.99, P = 0.034) and not receiving anticoagulation (OR = 0.24, 95% CI = 0.11–0.54, P < 0.001). Conclusion: Intravenous antimicrobial therapy for 28 days or longer carries a survival advantage over shorter duration of therapy and anticoagulation as an adjunctive treatment is an independent predictor of successful antimicrobial therapy. Disclosures: I. Raad, The University of Texas MD Anderson Cancer Center: Shareholder, Licensing agreement or royalty. The Unversity of Texas MD Anderson Cancer Center: Shareholder, Dr. Raad is a co-inventor of the Nitroglycerin-Citrate-Ethanol catheter lock solution technology which is owned by the University of Texas MD Anderson Cancer Center (UTMDACC) and has been licensed to Novel Anti-Infective Technologies LLC, in which UTMDACC and Licensing agreement or royalty.